2015
DOI: 10.3324/haematol.2014.109421
|View full text |Cite
|
Sign up to set email alerts
|

The novel  2-selective proteasome inhibitor LU-102 synergizes with bortezomib and carfilzomib to overcome proteasome inhibitor resistance of myeloma cells

Abstract: ABSTRACTby IRE-1a knockdown is characterized by decreased activation of the UPR and a less mature phenotype with a lack of fully developed ER. Likewise, myeloma cells adapted to bortezomib treatment in vitro (bortezomib-adapted cells) have a reduced rate of protein biosynthesis and a low activation state of the UPR. 20 Together, these data support a "low-IRE-1-a/XBP-1-model" of bortezomib resistance, the validity of which is supported by the identification of XBP1-negative, immature myeloma cell populations ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 33 publications
(44 reference statements)
6
45
1
Order By: Relevance
“…LU-102 is a β2-specific peptide vinyl sulfone developed by our group (Kraus et al, 2014), and NC-021 is a novel peptide epoxyketone that is a more potent β1 inhibitor than the previously published inhibitor NC-001 (Britton et al, 2009) (Fig. S1a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LU-102 is a β2-specific peptide vinyl sulfone developed by our group (Kraus et al, 2014), and NC-021 is a novel peptide epoxyketone that is a more potent β1 inhibitor than the previously published inhibitor NC-001 (Britton et al, 2009) (Fig. S1a).…”
Section: Resultsmentioning
confidence: 99%
“…Although Btz and Ixz can, at higher concentrations, inhibit the β1 site, neither drug inhibits the β2 site (de Bruin et al, 2016). We have developed specific inhibitors of the β1 and β2 sites and demonstrated that co-inhibiting either the β1 or β2 site increases the cytotoxicity of β5 inhibitors in MM cell lines (Britton et al, 2009; Geurink et al, 2013; Kraus et al, 2014; Mirabella et al, 2011). The β2 inhibitor LU-102 overcomes Btz and Cfz resistance in primary MM cells ex vivo, and also reduces xenograft tumor growth in Cfz-treated mice in vivo (Kraus et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, we have previously reported that the mutation of PSMB5 is involved in BTZ resistance in MM cells (Fig. 4a, b) [30], and others have reported several factors upregulated in BTZ-resistant MM cell lines, including IGF-1R [31], PSMB2 [32,33], germinal center B cell markers [34], and TXNRD2 [16]. Another reported reduced expression of the plasma cell differentiation marker [35,36] or XBP1 [37,38] in BTZ-resistant cells.…”
Section: What Factors Associate With the Sensitivity And Resistance Omentioning
confidence: 89%
“…As reported before, we noted that for both JJN3 (Figure C) and RPMI 8226 (Figure D) cells, the Rub999, Rub1024 and PR671A inhibitors selectively suppressed the CT‐L, C‐L and T‐L activities, respectively. Thus, as was suggested, the high percentage of cell death in MM cells achieved by BTZ and EPOX (and likely CFZ) is associated with co‐inhibition of more than one proteasomal peptidases. These findings also support the notion that the CT‐L activity is the rate limiting for protein breakdown and accordingly, selective inhibition of the β5 peptidase by Rub999 increased cell death, yet, as mentioned less effectively and at higher concentrations as compared to BTZ or EPOX, and likely CFZ …”
Section: Resultsmentioning
confidence: 75%